Analisis Penggunaan Batik Secara Efektif Pada Implementasi Produk Lokal: Perspektif Keberlanjutan Untuk Mendorong Ekonomi Warga Setempat - Sifa Nafis Salsabilla; Achmad Bhakti Nusa Pramana; Ainun Adila; Anindya Valentine; Galuh Attilargo; Ganjar Muhammad Ganeswara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Preserving local culture, especially batik, is an important aspect of sustainable development in Indonesia. This research aims to see how people in Indonesia realize how important it is to preserve batik culture, especially for the community to encourage local products. This research uses a qualitative descriptive method with primary data in the form of observations and interviews and secondary data in the form of literature studies, including books, journals and other internet sources. The research results found that efforts to preserve batik continue, driven by the government's commitment as a member of the UNESCO Creative Cities Network (UCCN). Through the implementation of the Sustainable Development Goals (SDGs), creative cities like Pekalongan can become models of sustainable development by combining aspects of creativity, arts education and cultural heritage preservation. In this way, local culture is not only a national identity, but also an instrument for achieving overall sustainable development goals.